A TENTATIVE 2D THERMAL MODEL OF CENTRAL INDIA ACROSS THE NARMADA-SON LINEAMENT (NSL) - Rai S.N.; Thiagarajan S. (My University, 2006)
This work deals with 2D thermal modeling in order to delineate the crustal thermal structure of central India along two Deep Seismic Sounding (DSS) profiles, namely Khajuriakalan-Pulgaon and Ujjan-Mahan, traversing the Narmada-Son-Lineament (NSL) in an almost north-south direction. Knowledge of the crustal structure and P-wave velocity distribution up to the Moho, obtained from DSS studies, has been used for the development of the thermal model. Numerical results reveal that the Moho temperature in this region of central India varies between 500 and 580 °C. The estimated heat flow density value is found to vary between 46 and 49 mW/m2. The Curie depth varies between 40 and 42 km and is in close agreement with the Curie depth (40±4 km) estimated from the analysis of MAGSAT data. Based on the present work and previous work, it is suggested that the major part of peninsular India consisting of the Wardha-Pranhita Godavari graben/basin, Bastar craton and the adjoining region of the Narmada Son Lineament between profiles I and III towards the north and northwest of the Bastar craton are characterized with a similar mantle heat flow density value equal to ~23 mW/m2. Variation in surface heat flow density values in these regions are caused by variation in the radioactive heat production and fluid circulation in the upper crustal layer. © 2005 Elsevier Ltd. All rights reserved.
Keywords: 2-D THERMAL MODEL; CRUSTAL THERMAL STRUCTURE; CURIE DEPTH; HEAT GENERATION; MOHO; NARMADA-SON LINEAMENT; SURFACE HEAT FLOW